Meropenem Determination in Human Plasma by LC-MS/MS and Evaluation for Therapeutic Drug Monitoring in ICU Patients - Dita Amalia; Endang Lukitaningsih; Akhmad Kharis Nugroho; Ika Puspitasari (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Meropenem is a broad-spectrum beta-lactam antibiotic widely used in intensive care units (ICUs) for severe bacterial infections. Therapeutic drug monitoring (TDM) is essential to optimize its dosing, ensuring effective bacterial eradication while minimizing toxicity and resistance.This study aimed to determine meropenem concentrations in human plasma using LC-MS/MS and evaluate its application in TDM for ICU patients. Meropenem concentrations in plasma samples from ICU patients were analysed using a validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. The study included 40 plasma samples from 20 patients receiving meropenem continuous infusion. Validation followed ICH M10 (2022) guidelines, assessing specificity, accuracy, precision, stability, and dilution integrity. The developed LC-MS/MS method demonstrated high selectivity, sensitivity, and linearity (r = 0.9930.996) over the 102000 ng/mL range. Accuracy and precision met ICH M10 acceptance criteria, with %CV 15%. All ICU patients maintained %fTMinimum Inhibitory Concentration (MIC) 40%, ensuring adequate bacterial eradication. Notably, patients with renal impairment required dose adjustments, while those with high creatinine clearance needed increased dosing. The validated LC-MS/MS method is suitable for meropenem TDM in ICU patients, allowing individualized dosing adjustments to optimize therapy.